Localization and treatment of lingual venous and arteriovenous malformations. (February 2014) - Wiegand, Susanne; Tiburtius, Janna; Zimmermann, Annette P; Güldner, Christian; Eivazi, Behfar; Werner, Jochen A
Venous and arteriovenous malformations of the tongue can cause haemorrhage, airway obstruction, difficulties in chewing and swallowing, speech problems as well as orthodontic abnormalities. The purpose of the present study was to evaluate their exact topography, clinical features, morphologic aspects and management. A retrospective review on all patients with venous and arteriovenous malformations of the tongue who presented between 1998 and 2010 was performed. Medical records were analysed with respect to age and sex distribution, exact localization, symptoms and clinical presentation, management and treatment outcome. Forty-four patients with tongue malformations were analysed. The malformations affected all areas of the tongue as well as the base of the tongue without predilection areas. Nd:YAG laser and CO2 laser therapy provided good results primarily in localized malformations, while in advanced malformations the management was multi-modal since a complete surgical excision was often impossible. The hypothesis that vascular malformations of the tongue occur more frequently along the course of the feeding vessels cannot be confirmed. The therapeutic approach is determined by the exact topography, haemodynamic properties, morphologic aspects and related clinical symptoms as well as patient-specific features.